Analisis Pemilihan Saham oleh Investor Asing di Bursa Efek Indonesia - CHANDRA, RUDY (UI Scholars Hub, 2011)
The first objective of this study is to analyze what kind of sector industry which is selected by foreign investor in Indonesia. Second, to analyze what kind of financial firm characteristic of stocks which is selected by foreign investor. This study used a quantitative approach by using secondary data from financial reports and historical data from Indonesian Stock Exchange. Researcher used multivariate regression to analyze the correlation between stocks selected by foreign investor with financial firm characteristic. Based on the result, foreign investor are overweight stocks from Consumer Goods Industry. Dividend yield, beta, and book to market are financial firm characteristic which is significantly influence the stock selection by foreign investor.